Cardioprotective medication adherence among patients with coronary heart disease in China: a systematic review. Issue 2 (24th June 2019) - Ni, Zhao; Dardas, Latefa; Wu, Bei; Shaw, Ryan
Abstract : In China, poor cardioprotective medication adherence is a key reason for the high mortality rate of coronary heart disease (CHD). The aims of this systematic review are to (1) describe and synthesise factors that influence medication adherence among Chinese people with CHD, (2) evaluate the current status of intervention studies, and (3) discuss directions of future research to improve medication adherence. A comprehensive search using PubMed, Cumulative Index to Nursing and Allied Health Literature, Embase, Scopus, Global Health and PsycINFO was undertaken to describe poor adherence in China. Thirty-three eligible articles were included in the study. The review shows that there are multiple contributing factors to poor medication adherence, including patients' sociodemographic characteristics, health status and medication characteristics. In addition, from patients' perspective, lack of medication-related knowledge, such as the name, function, dosage and frequency, contributes to poor adherence. From physicians' perspective, a gap exists between CHD secondary prevention guidelines and clinical practice in China. Follow-up phone calls, educational lectures, booklets and reminder cards were common methods found to be effective in improving medication adherence. This systematic review indicates that cardioprotective medications were commonly prescribed as secondary prevention medication to patients with CHD in China, but adherence to these medications gradually decreased during a follow-up period. Therefore, more research should be conducted on how to establish high-quality health educational programmes aimed at increasing patients' medication adherence.